Legal polycentrism and contractarianism - Wiśniewski, Jakub Bożydar (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
According to the contractarian perspective, a public good can be thought of as not so much a good that meets the technical neoclassical criteria of non-rivalness and non-excludability, but as one that is produced on a purely contractual basis, thus necessarily increasing the utility of all the involved parties. In this paper, by critically examining Nozick’s “emergent” contractarianism and Buchanan’steleological contractarianism, I shall argue that no such contractual origin can be plausibly attributed to territorial monopolies of force, and that therefore legal monocentrism — the view that the public goods of law and defense can be provided exclusively by territorial monopolies of force — fails the relevant efficiency test as conceived on a contractarian basis. This, in turn, implies that legal polycentrism, one of whose constitutive features is precisely its unambiguously voluntary and contractual character, should be considered as a superior system in this context
Keywords: legal polycentrism; contractarianism; public goods; public choice; conceptual unanimity; institutional entrepreneurship